EFFECTIVENESS OF NURSE-LED SMOKING CESSATION PROGRAMS - Amrah Maqbool Almaqadi, Amna Ali Mahnashi, Modhi Nasser Alshammari, Mariam Mahmoud Albaiji, Amsha Naser Alshammari, Wejdan Ahmad Alwadei, Rahmah Mohammed Alhawsawi, ,; Mansour Thufayl Alanazi, Ahad Falah Jadaan Al Dhafiri, Abeer Naseer Alrhiman, Aishaa Faihan Almutairi, Abdulrahman Rashid Almosayed, Wedad Egab Alrashed, Rabah Raja Alharbi, Hassan Mohammed Tomihi, (Chelonian Research Foundation, 2022)
Approximately 50% of smokers succumb to diseases directly caused by smoking. Cessation of smoking may mitigate these issues. Smoking cessation therapies include a range of methods aimed at assisting smokers in effectively quitting. Research indicates that hospitalization is a valuable chance for nurses to assist patients in quitting smoking due to the implementation of No Smoking policies. The objective of this research was to elucidate the role of nurses in the design and execution of nursing interventions pertaining to smoking cessation. A comprehensive literature review was conducted using various databases including Web of Knowledge, ProQuest, Medscape, MedlinePlus, Ovid SID, Magiran, PubMed, and Science Direct. The search covered the period from 1990 to 2015 and focused on the following keywords: role of nursing in smoking cessation, nursing intervention in smoking cessation, smoking cessation, smoking quitting, and interventions planned by nurses. The majority of research used various approaches, such as manuals, booklets, brochures, training materials, and printed instructional materials, as well as audio and video files. Several research included nicotine replacement strategies, including the use of nicotine skin patches, nicotine chewing gum, or bupropion. In addition, 17 investigations were undertaken by telephone to follow up with patients after they were discharged from the hospital. Nurses' interventions for smoking cessation are crucial in facilitating effective smoking cessation among patients. Nurses may use a range of interventions based on the patient's specific state and diagnosis of various illnesses. Keywords: nursing in smoking cessation, nursing intervention, smoking cessation, smoking quitting, nurses, review.